Driving Foreign Tourist to Bandung: The Traveloka Travel Friends Project Design - Mochamad Dival Harsyauqi; Kurnia Khafidatur Rafiah (Jurnal Manajemen Bisnis, 2023)
The goal of the Traveloka Travel Friends Bandung campaign is to increase demand for Traveloka's lodgings through the use of social media channels like TikTok. However, the content that the Traveloka Travel Friends Bandung group shares via TikTok's For You Page (FYP) function is not perfect in terms of reaching international visitors. To assess where things are now, we use the SOSTAC method, which stands for "Situation Analysis; Objectives; Strategy; Tactics; Action; and Control." According to the data, the Traveloka Travel Friends campaign has successfully penetrated the local market. The data provides clear evidence of this, showing a range value of 97-100% with Indonesian origins. However, statistics show that only 2% of viewers come from Malaysia, making this initiative less than ideal in terms of efficiently engaging an international audience. This research uses a business model canvas to outline a strategy for increasing domestic and international visitors to Bandung. In this research, we lay out several development strategies for maximising these possibilities. All content will have English subtitles, an activity programme called "Wara Wiri Bandung" will be launched, and joint activities will be planned with other organisations.